Protein Kinase Inhibition, Antibacterial Activity, and Characterization of Phytoextract-Mediated Silver Nanoparticles Using Aqueous Extracts of Ifloga spicata. (16th June 2022) - Gul, Ahmad; Wahab, Abdul; Fozia, Fozia; Shah, Syed Majid; Gul, Rukhsana; Ali, Jamshed; Khan, Nauman Rahim; Ahmad, Ijaz; Ahmad, Nisar; Zia, Muhammad; Ullah, Riaz; Alotaibi, Amal; et al.
Abstract : This research work was focused on green synthesis of silver nanoparticles (Ag-NPs) employing an aqueous plant extract of Ifloga spicata . The extract of plant used in the silver nanoparticle synthesis served as a stabilizing and reducing agent. The silver nanoparticles were characterized via various techniques such as X-ray diffraction (XRD) technique, scanning electron microscopy (SEM), Fourier transform infrared (FT-IR) spectroscopy, and UV-visible spectroscopy. The FT-IR analysis showed an identification of functional groups of biomolecules present in plant extract like O-H stretching of phenolic compounds and the C-H stretch of alkanes, C=O is stretching vibration of carbonyl, C-N is stretching of amines and amides, and the C-O is stretching of ester that facilitates the formation of Ag-NPs. The spherical geometry and crystalline morphology with an average crystal size of 15-28 nm of Ag-NPs were revealed using SEM and XRD analysis, respectively. The stability of Ag-NPs was checked through changing the pH and temperature of the reaction mixture. It was examined that synthesized Ag-NPs were stable at 60°C temperatures and nearly neutral pH 8. The synthesized Ag-NPs also exhibit potential antibacterial activity that were investigated against a selected bacterial pathogens, like E. aerogens, B. bronchiseptica, and S. typhimurium. The silver nanoparticles exhibited a maximum zone of inhibition of 18.1 ± 1.73  mm, 14.3 ± 1.18  mm, and 19.5 ± 1.30  mm against E. aerogens, B. bronchiseptica, S. typhimurium, respectively. The synthesized Ag-NPs exhibit promising protein kinase inhibition at 200 ( μ g/mL) as compared to plant extracts.